Manajemen Aset Tanah dan Bangunan dalam Meningkatkan Pendapatan Asli Desa oleh Pemerintah Desa Sayang, Kecamatan Jatinangor - Anisa Wulan Sari; Raden Ahmad Buchari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes land and building asset management in increasing Village Original Revenue (PADes) in Sayang Village, Jatinangor, using a qualitative approach based on Mardiasmo’s asset management theory and Permendagri No. 1/2016. Data were col- lected through interviews, observations, and documentation. Findings indicate that as- set management has boosted PADes from Rp36.5 million (2021) to Rp174.5 million (2024) through strategies like converting land into kiosks and parking areas. However, chal- lenges include incomplete asset inventories, uncertified assets, and limited use of the SIPADES application due to technical issues and inadequate training. Recommenda- tions include accelerating asset certification, optimizing SIPADES, and providing regular training to enhance efficiency and transparency for sustainable village development.